The Model of Digital Communication and Supply Chains For The Tourism Industry - Deden Komar Priatna; Winna Roswinna (Greenation International Journal of Tourism and Management, 2023)
This research aims to understand the effects of digital communication, supply chain services and tourism on the decision to visit Indonesia. A quantitative approach was used to gather data through 400 survey participants. This study took the form of a methodology, design and approach framework. It analyzed the effect of digital communication, supply chain services and tourism with Quantitative data collected from Indonesia tourists and social media users. Probability sampling was used to collect data in a random manner. This method was used in a study that used Structural Equation Modeling and the SEM-PLS method. Results showed that digital supply chain and communication services had a significant positive impact on the interest of visitors. This led to a significant increase in their choice to visit a location. Additionally, this led to a significant increase in the impact of their decision on whether or not to visit.